A Review of Solar-Powered Boat Development - Kurniawan, Adi (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2016)
Research in the application of renewable energy has intensified in recent years. The possibility of petroleum extinction in the future is forcing researchers to enhance the utilization of renewable energy resources as substitute for fossil fuel-based technologies in all fields. Ships as one of the most important transportation in the world also require diesel oil as fuel for main propulsion systems and for diesel generators which supply electrical needs. Solar energy has been considered as the most suitable renewable energy resources to substitute the role of fuel in the ships. In this paper, the latest research on the utilization of solar energy in the ship are presented and analyzed to provide information for the researchers who developed the technology of solar-powered boat